West side story - Wise, Robert 1914-.; Mirisch Pictures (Firm).; Seven Arts Productions (Quezon City Viva Video, 2001)
This musical sets the tragedy of Romeo and Juliet against a backdrop of the rivalry of two street gangs, the Sharks and the Jets, in New York of the 1950s. A young woman who is sister to the Sharks leader has her first taste of love with the former head of the Jets.
Disc 1 (55 min.) -- disc 2 (58 min.) -- disc 3 (39 min.)
VCD.
Based on the stage play produced by Robert E. Griffith and Harold S. Prince by arrangement with Roger L. Stevens ; book by Arthur Laurents.
Directed by Robert Wise and Jerome Robbins ; screenplay by Ernest Lehman.
Natalie Wood, Richard Beymer, Russ Tamblyn, Rita Moreno.
Academy Awards Winner, Best Actor in a Supporting Role (George Chakiris); Best Actress in a Supporting Role (Rita Moreno) ; Best Director (Robert Wise, Jerome Robbins) ; Best Music, Scoring of a Musical Picture (Saul Chaplin, Johnny Green, Sid Ramin, Irwin Kostal) ; Best Picture (Robert Wise), 1962.
Keywords: Gangs -- New York (State) -- Drama; First loves -- Drama; Feature films; Musical films